The Gap between Theological Understanding and Digital Technology Use Practices among Christian Students in Indonesia - Telaumbanua, Elvy Artalenta; Wijiati, Wahyu; Waruwu, Dermawan (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2026)
The rapid development of digital technology has significantly transformed the lives of Christian university students in academic, social, and spiritual dimensions. This study aims to analyze the gap between theological understanding and the actual practices of digital technology use among Christian students through a library research approach. Employing a qualitative method, the study examines scholarly literature related to the integration of Christian faith, digital technology, digital spirituality, and the digital behavior of Christian students in Indonesia. Data were analyzed using content analysis with a descriptive-critical approach. The findings reveal that Christian students generally possess a sound theological understanding of the importance of using digital technology in accordance with Christian values such as love, responsibility, honesty, and self-control. However, their actual digital practices often fail to fully reflect these values. The gap is evident in the tendency to use social media primarily for entertainment, self-presentation culture, digital addiction, declining spiritual discipline, and various online behaviors that do not consistently align with Christian ethical principles. The factors contributing to this gap include internal factors such as weak spiritual discipline, limited spiritual motivation, and insufficient self-control, as well as external factors including social media culture, digital distractions, peer pressure, and the lack of digital spiritual mentoring. These findings indicate that integrating Christian faith into digital technology use requires more than theological knowledge; it also demands the formation of Christian digital character, the strengthening of digital spirituality, and the development of faith-based digital literacy. Therefore, Christian Religious Education should adopt a holistic approach to bridge the gap between theological understanding and digital practices among Christian students in the digital age.